The importance of accounting for atmospheric effects in the application of ndvi and interpretation of satellite imagery supporting archaeological research: the case studies of Palaepaphos and nea Paphos sites in Cyprus - Alexakis, Dimitrios; Papoutsa, Christiana; Papadavid, George; Hadjimitsis, Diofantos G.; Agapiou, Athos (My University, 2011)
This paper presents the findings of the impact of atmospheric effects when applied on satellite images intended for supporting archaeological research. The study used eleven multispectral Landsat TM/ETM+ images from 2009 until 2010, acquired over archaeological and agricultural areas. The modified Darkest Pixel (DP) atmospheric correction algorithm was applied, as it is considered one of the most simple and effective atmospheric corrections algorithm. The NDVI equation was applied and its values were evaluated before and after the application of atmospheric correction to satellite images, to estimate its possible effects. The results highlighted that atmospheric correction has a significant impact on the NDVI values. This was especially true in seasons where the vegetation has grown. Although the absolute impact on NDVI, after applying the DP, was small (0.06), it was considered important if multi-temporal time series images need to be evaluated and cross-compared. The NDVI differences, before and after atmospheric correction, were assessed using student’s t-test and the statistical differences were found to be significant. It was shown that relative NDVI difference can be as much as 50%, if atmosphere effects are ignored. Finally, the results had proven that atmospheric corrections can enhance the interpretation of satellite images (especially in cases where optical thickness of water vapour is minimized ≈ 0). This fact can assist in the detection and identification of archaeological crop marks. Therefore, removal of atmospheric effects, for archaeological purposes, was found to be of great importance in improving the image enhancement and NDVI values.
Keywords: Atmospheric correction; Crop marks; Modified darkest pixel algorithm; Vegetation indices